2014
DOI: 10.1093/arclin/acu016
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Mutations and Cognition: A Case-Series Report

Abstract: Mutations in the mitochondrial genome can impair normal metabolic function in the central nervous system (CNS) where cellular energy demand is high. Primary mitochondrial DNA (mtDNA) mutations have been linked to several mitochondrial disorders that have comorbid psychiatric, neurologic, and cognitive sequelae. Here, we present a series of cases with primary mtDNA mutations who were genotyped and evaluated across a common neuropsychological battery. Nineteen patients with mtDNA mutations were genotyped and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Many patients with primary mtDNA mutations demonstrated pronounced cognitive deficits quite similar to those commonly seen in AD [69], which supports a critical role of mtDNA in proper cognitive function. Interestingly, it is reported that in families with a history of dementia, a consistently identified risk factor for AD, maternal transmission is significantly more frequent than paternal transmission.…”
Section: Disturbed Mitochondrial Genomic Homeostasis In Admentioning
confidence: 60%
“…Many patients with primary mtDNA mutations demonstrated pronounced cognitive deficits quite similar to those commonly seen in AD [69], which supports a critical role of mtDNA in proper cognitive function. Interestingly, it is reported that in families with a history of dementia, a consistently identified risk factor for AD, maternal transmission is significantly more frequent than paternal transmission.…”
Section: Disturbed Mitochondrial Genomic Homeostasis In Admentioning
confidence: 60%
“…Inczedy-Farkas et al [22] found average FSIQ within normal limits, and lower PIQ than VIQ scores. Pronounced PIQ deficits were observed in processing speed and visuospatial functioning.…”
Section: Larger-scale Systematic Investigations Of Cognitionmentioning
confidence: 94%
“…Interestingly, oxidized mtDNA activates pro-inflammatory cytokines ( Adzic et al, 2016 ) and increased inflammation is known to play a role in the development of depressive symptoms (e.g., Brymer et al, 2018 ; Wang et al, 2018 ). Variations in mtDNA have also been shown to cause cognitive impairments in mice ( Sharpley et al, 2012 ) and in humans ( Inczedy-Farkas et al, 2014 ; Petschner et al, 2018 ), and cognitive deficits are a common symptom associated with depression.…”
Section: Geneticsmentioning
confidence: 99%